Decomposition of fluorophosphoryl diazide: a joint experimental and theoretical study1. Issue 9 (7th March 2015) - Li, Dingqing; Li, Hongmin; Zhu, Bifeng; Zeng, Xiaoqing; Willner, Helge; Beckers, Helmut; Neuhaus, Patrik; Grote, Dirk; Sander, Wolfram
<x xml:space="preserve">Abstract</x> The stepwise decomposition of fluorophosphoryl diazide (FP(O)(N3)2), via nitrene (FP(O)(N3)N) and the cyclic intermediate (FP(O)N2), was experimentally and theoretically studied.